An Analysis of Assertive Speech Act in Donald Trump Inauguration 2025 Speech in YouTube - I Made Suartika; Ida Ayu Putri Gita Ardiantari (Universitas Islam Negeri Palopo, 2025)
This study aims to identify and explain the types and functions of assertive speech acts used in Donald Trump’s 2025 inauguration speech. The data were taken from a video entitled “Donald Trump Inauguration Speech 2025” uploaded on the official CNN YouTube Channel (accessed on February 5, 2025, with a duration of 23 minutes and 14 seconds, and 5.8 million views at the time of analysis). This research employs a qualitative descriptive approach, referring to Searle’s (1979) theory of illocutionary speech acts. The findings show that out of 56 assertive utterances, there are five types of assertive speech acts: claiming (25%), stating (21.43%), complaining (19.64%), reporting (17.86%), and explaining (16.07%). The claiming type was the most frequently used, indicating that Trump often emphasized his beliefs and evaluations of the political situation to strengthen his message and shape the audience’s perception. This study expands the application of speech act theory in political contexts and provides insight into how language is strategically used to build legitimacy, trust, and a leader’s image.